Elucidating neuropharmacological implications of vincetene: a multi-target computational study on ataxia, encephalitis, and meningitis - Prameela, Athira; Radhakrishnan, Arunkumar; Krishnasamy, Thenmozhi (Prospects in Pharmaceutical Sciences, 2025)
Ataxia, meningitis, and encephalitis are exemplars of acute neurological ailments that are convoluted and often fatal, with limited therapeutic options and multifactorial pathophysiology. The polypharmacological adeptness and outstanding safety profiles of plant-derived bioactive molecules make them intriguing candidates for neuroprotective drug research. Vincetene, an isoquinoline alkaloid identified in species of the genera Vincetoxicum and Cynanchum, was selected for this investigation and evaluated for its neurotherapeutic feasibility using a comprehensive in silico approach. Pharmacokinetic profiling using SwissADME anticipated guaranteed drug-likeness, blood–brain barrier permeability, high gastrointestinal absorption, and no interaction with P-glycoprotein. Vincetene justified multiple drug-likeness rules (Lipinski, Veber, Ghose, Egan, Muegge) and demonstrated a bioavailability score of 0.55. Toxicological evaluation via ProTox-II recommended non-carcinogenic, non-mutagenic, and non-cytotoxic properties, but implied potential hepatotoxicity, neurotoxicity, immunotoxicity, and respiratory toxicity. Network pharmacology assessment pinpointed 49 intersecting genes between vincetene targets and disease-related genes. Hub genes divulged through protein–protein interaction networks included PI3KCA, AKT2, AKT3, MTOR, and HSP90AA1. Gene ontology and pathway enrichment analysis signified the contribution of vincetene to PI3K-Akt, HIF-1, and ErbB signaling pathways, which are decisive for neuronal survival and stress response. Molecular docking established stable binding to target proteins 2Z83 (-7.6 kcal/mol), 5KTR (-6.1 kcal/mol), and 1Q5K (-8.8 kcal/mol). These findings suggest that vincetene exerts multi-targeted neuroprotective effects and holds promise as a neurotherapeutic lead compound. Overall, this study provides the tactical repositioning of vincetene for the management of complex neurological disorders, paving the way for future experimental research.